THE DETERMINATION OF DISPLACEMENTS ON THE SURFACE OF THE HALF SPACE CAUSED BY AN INNER CRACK NUCLEATION - Skalskiy, V. R.; Stankevich, O. M. (Science and Transport Progress, 2010)
The dynamic problem on determination of the wave field of displacements on the surface of the elastic halfspace caused by an inner crack nucleation is presented. The problem is solved using boundary integral equations. The relationships between the parameters of displacements of the body surface points and the functions of opening of the defect walls are derived and analyzed.